Postulating the Modality of Integrative Taxonomy in Describing the Cryptic Congener Pampus griseus (Cuvier) and Systematics of the Genus Pampus (Perciformes: Stromateidae) - Roul, Subal Kumar; Jeena, N. S.; Kumar, Rajan; Vinothkumar, R.; Rahangdale, Shikha; Rahuman, Summaya; Ghosh, Shubhadeep; Rohit, Prathibha; Gopalakrishnan, Achamveetil (Frontiers in Marine Science, 2021)
Pomfrets (genus Pampus), a highly commercial fishery resource distributed in the Indo-Western Pacific that includes Lessepsian migrants, have witnessed a series of systematic reforms. In this study, based on comprehensive sampling spanning type localities and coevals in the Northern Indian Ocean, the cryptic and valid species Stromateus griseus is resurrected from the synonymy and re-described as Pampus griseus (New Combination) based on 35 specimens from the Bay of Bengal, corroborated by a molecular analysis, which indicated a confined distribution of the species. The Bayesian phylogeny of the genus was reconstructed, incorporating redressed barcodes (582 nucleotides) and concatenated mitochondrial gene sequence data (1,822 nucleotides) generated from the recorded species P. candidus, P. chinensis and the neophyte along with sequences from GenBank entrusting the latest literature. The phylograms differed in topology as for seven valid species, and the one predicated on the concatenated data erected a highly supported polytomous clade for the P. cinereus complex (P. griseus, P. cinereus, and P. candidus) which shares synapomorphies. Pampus argenteus and P. minor, together, formed a sister clade to the rest. Climate-driven vicariant events during glacial epochs and the Indo-Pacific Barrier effect can be the drivers behind the Indian and Pacific Ocean sister lineages in P. chinensis. A multivariate analysis isolated the cryptic species from its congeners. This article portrays the systematics revision of genus Pampus with an integrative taxonomic approach compiling distinctive molecular, morphological, and anatomical features, revised key for species identification, taxonomic archives of Indian stromateids, and winds up with specific remarks.